Isaiah Berlin and the role of education: from Riga to Oxford - Silva, Elisabete Mendes (2015)
Being the result of a lecture to Latvian students in May 2011, this article aims at introducing Isaiah Berlin, who was born in Riga in 1909. The focus will be on the man and the intellectual, how his life experience (his childhood in Russia and the fact that he was an emigrant in Britain) affected his intellectual route, and how he became a defender of liberalism and value-pluralism. Furthermore, special attention will also be given to Berlin’s opinions on Education, the way he regarded the educational problems of his time and how education should be enhanced in order to escape from obscurantism and dogmatism towards a freer intellectual life and also to develop capacities for thought and feeling. Berlin believed education, and particularly university education, could be a powerful means to achieve these ends.